Physiological profile and energy expenditure of high level badminton players. - Esposito, F.; Pugliese, L.; Rampichini, S.; Limonta, E.; Gianfelici, A.; La Torre, A. (World Badminton Federation, 2016)
Knowledge about cardiorespiratory and metabolic demands, as well as activity profile during competitions provides usually the basis for adequate performance assessment and evidence-based design of training programs. Despite the well-known popularity of badminton, information on physiological players' profile and energy expenditure during this activity are still very limited. The few papers present in the literature focused on heart rate (HR) (Cabello Manrique & Gonzalez-Badillo, 2003; Cabello Manrique, Padial, & A., 2004; Ghosh, Mazumdar, & Goswami, 1990; Kim, 2002) and blood lactate concentration during the match (Cabello Manrique & Gonzalez-Badillo, 2003; Cabello Manrique et al., 2004). Only two investigations included also pulmonary oxygen uptake (.....2) measurement (Faccini & Dai Monte, 1996; Faude et al., 2007). Taking together, these investigations suggest that badminton can be defined as an intermittent sport activity characterized by short duration-high intensity efforts, followed by short recovery periods with very high physiological demand.